Active earth pressure on non-yielding retaining walls with geofoam blocks and granular backfills. (March 2022) - Fan, Kewei; Yan, Jun; Zou, Weilie; Han, Zhong; Lai, Zhiqiang
Abstract: Geofoam blocks are typically used as buffer layers behind non-yielding retaining walls to reduce the lateral earth pressure. The interaction between the geofoam blocks and the backfills is essential for the determination of the earth pressure and thus the design of the geofoam blocks. In this study, two-dimensional model tests of aluminum rod mass as filling soils were conducted to study the lateral earth pressure acting on a non-yielding wall with geofoam blocks. The following observations were obtained: (i) the compression of the geofoam blocks increases linearly or bi-linearly along the wall height, depending on the stress level; (ii) a clear slip surface can be observed in the aluminum rod mass, which is consistent with the assumptions of the Coulomb's active earth pressure theory. Considering the deformation of the geofoam blocks and the backfills, a series of equations were proposed for calculating the earth pressure on the non-yielding wall with geofoam blocks and granular backfills. The earth pressure calculated by the proposed equations agrees well with the experimental measurements.